Expertise Collaboration & Data Integration in Industries - Kumar, Anuj (PREPARE@u® | IEI Conferences, 2021)
Tracing clues of revolutionary moments in the recent past that have given economic development a breakthrough leap worldwide, one cannot forget to mention the phrase Fourth Industrial Revolution[1] (4IR or Industry 4.0) which was introduced by a team of scientists developing a high-tech strategy for the German government and was later introduced to a wider audience through including it in the theme “Mastering the Fourth Industrial Revolution” of World Economic Forum Meeting for the year 2016 held in Switzerland. While institutionalizing new ventures of innovation is widely being considered as the way ahead for India to achieve its aspirations of becoming a 5 trillion economy, exploring ways towards extracting maximum yield out of its existing industrial resources is another important pillar which is needed to be given equal attention upon. Undoubtedly, the next leap of industrial transformation lies in combining the power and value of data. Interestingly, data is already there, industry owners have struggled to see through or make sense, to access or harness its value. As the theme here is Engineers for Viable Technology and 5 Trillion Economy, which is a Techno-Philosophical subject, let’s explore the correlation between the technical human resource and their scientific deliverables.